Multilevel Step-Down Resonant Switched-Capacitor Converters With Full-Range Regulation - Xie, Wenhao; Brown, Benjamin Y.; Smedley, Keyue Ma (IEEE transactions on industrial electronics (1982), 2021)
Multilevel resonant switched-capacitor converters (RSCCs) have drawn attention in large step-down voltage conversion but are hindered in a wide area of applications due to limited voltage regulation range. A new full-range regulation (FR) method for multilevel step-down RSCCs is proposed in this article. As an example of the proposed FR method, the fixed on-time modulation for modified Dickson RSCC is provided. In addition to full-range voltage regulation, the multilevel RSCCs with the proposed FR method feature complimentary driving signals, zero voltage switching turn- on for switches, zero current switching turn- off for diodes, even switch voltage stress, even diode voltage stress, high active switch utilization, high efficiency, and high power density. A modified Dickson RSCC prototype was built to validate the proposed FR method. The proposed FR method is further extended to series-parallel RSCCs and Fibonacci RSCCs.